Abdülkâdir Geylânî (k.s.)’den Yolun Esasları: 52 Sohbet Cilâü’l-Hâtır - Çelik, Halil İbrahim (İstanbul Sabahattin Zaim Üniversitesi, 2023)
Cilâü'l-hâtır, Abdulkadir Geylânî’nin vaazlarını bir araya getiren el-Fethu’r-Rabbânî gibi sohbetlerden oluşan müstakil bir derleme hatta onun devamı niteliğindedir. Bu vaaz ve sohbetler tasavvufla ilgilidir. Konular daha ziyade masivayı terk ve gizli-açık her türlü şirkten uzaklaşma üzerinedir. Mevzular işlenirken âyet ve hadislere sıklıkla müracaat edilmiştir. Başka bir deyişle Cilâü’l-hâtır, Abdulkâdir Geylânî’nin yaklaşık iki buçuk aylık zaman zarfındaki vaazlarından oluşmaktadır. Vaazları derleyen şahsın kimliği belli değildir. İlk sohbetin tarihi 9 Receb 546/22 Ekim 1151, sonuncunun ise 24 Ramazan 546/4 Ocak 1152’dir.

Cilâü'l-hâtır is an independent compilation of conversations such as al-Fethu'r-Rabbani, which brings together Abdulkadir Geylani's sermons, and is even a continuation of it. These sermons and conversations are about sufism. The subjects are mostly about abandoning the plain and avoiding all kinds of secret and open polytheism. Verses and hadiths were frequently used while the subjects were being studied. In other words, Cilâü'l-hâtır consists of the sermons of Abdulkadir Geylani over a period of approximately two and a half months. The identity of the person who compiled the sermons is unknown. The date of the first conversation is 9 Rajab 546/22 October 1151, and the last one is 24 Ramadan 546/4 January 1152.
Foundations of the Path according to Abdulqadir Gilani: 52 Discourses forPurification of the Heart
Keywords: Geylâni; Tasavvuf; Zühd; İslam; Cilâü'l-hâtır; Geylani; Sufism; Zuhd; Islam; Cilâü'l-hâtır